Making Waves: towards a harmonized approach for monitoring antimicrobial resistance in European surface waters - P. Krzeminski; C.U. Schwermer; M. Anglès d’Auriac; H. Bürgmann; H. Schmitt; J. Vierheilig; M. Gjeitnes; S.J. Moe; X. Bellanger; R. Carapeto García; P. Crespo Iniesta; C. Dagot; et al. (Water Research, 2026)

Successful outcome of open distal interphalangeal joint luxation in equids treated by surgical debridement without internal implants - L. C. Ferrari; E. V. P. Apolonio; S. L. de Oliveira-Gonçalves; A. L. A. Rambo; J. V. Bergamasco; J. M. Alonso; M. J. Watanabe; A. L. G. Alves (Veterinary Research Communications, 2026)
Introduction The distal interphalangeal joint (DIPJ) plays a crucial role in the function of the hoof and digit. Dislocations and subluxations in this region are rare and primarily of traumatic origin. Case Report This case report aims to describe two unusual cases of open DIPJ dislocation, including clinical presentation, diagnostic workup, treatment, and long-term follow-up. Both animals presented with open traumatic distal interphalangeal joint (DIPJ) luxation. In Case 1, the animal received initial care on the property 5 h post-trauma and presented with joint exposure and articular surface contact with the ground. In Case 2, the animal was referred to the veterinary hospital without prior care, 3 h post-trauma, but there was no contact of the articular surface with the ground. Both animals showed grade 5/5 lameness (AAEP). The animals underwent general anesthesia, joint lavage, regional intravenous perfusion with antibiotics, debridement of devitalized tissues, skin synthesis, and immobilization with synthetic casting. During immediate recovery and hospitalization, a grade 4/5 lameness persisted. Long-term radiographic control revealed the development of degenerative joint disease in both animals. After 3 and 2 years, respectively, animals 1 and 2 showed persistent lameness (grade 2/5) with an absence of local sensitivity. Conclusion The conservative treatment employed in these cases of open DIPJ luxation proved effective for the maintenance of the patients’ lives, and although the infectious pathological process invariably progressed to osteoarthritis, the evolution of the clinical conditions allowed for light exercise and maintenance of reproductive activity.

Bridging soil mapping units and digital soil mapping through probability-driven machine learning: an uncertainty-aware framework for soil class prediction in Antarctica - Rafael G. Siqueira; Cássio M. Moquedace; Márcio R. Francelino; Carlos Ernesto G.R. Schaefer; Roberto F.M. Michel; Daniela Schmitz; Flávia R. Ferrari; Caroline Delpupo; Eduardo O. Senra; Heitor P. Palma; Daniel N. Krum; Fábio S. de Oliveira; et al. (CATENA, 2026)

Aging impact on canine extracellular vesicles production, size, and miRNA content - Clara Luna Marina; Alexandra Mazer Greuel; Lucas de O. Las-Casas; Evilly Lopes-Gomes; Sabrina Simplício de Araújo Romero Ferrari; Marcio Lourenço Rodrigues; Flavia C. G. dos Reis; Anamélia Lorenzetti Bocca; Simoneide Souza Titze-de-Almeida; Fernando Francisco Borges Resende; Fabiano José Ferreira de Sant’Ana; Ricardo Titze-de-Almeida (Veterinary Research Communications, 2026)
Increasing life expectancy has been accompanied by a higher prevalence of age-associated conditions, underscoring the need to better understand biological mechanisms of aging and to identify accessible biomarkers. Extracellular vesicles (EVs) are lipid-bilayer vesicles that mediate intercellular communication by transporting proteins, lipids, and regulatory RNAs, including microRNAs (miRNAs). Here, we investigated whether the abundance, morphology, and molecular cargo of plasma-derived EVs differ between young and senior dogs. Blood samples were obtained from 24 clinically healthy dogs in Gama (Federal District, Brazil), and plasma EVs were isolated by sequential centrifugation, filtration through a 0.22 μm filter, and ultracentrifugation. EVs concentration and size distribution were assessed by nanoparticle tracking analysis (NTA), morphology by transmission electron microscopy (TEM), and cargo by quantification of total protein and sterols using commercial assays. In addition, we quantified miR-19b, miR-29c, miR-7, miR-155, and miR-21 by Real Time Quantitative Polymerase Chain Reaction (RT-qPCR). Senior dogs exhibited a lower plasma EV yield and greater size heterogeneity, with a higher proportion of larger EVs. Total protein and sterol content per starting plasma volume were reduced in the senior group; however, sterol normalized per EV was increased, consistent with compositional remodeling of circulating vesicles with age. Finally, EV-associated miRNA levels were reduced in senior dogs, particularly miR-19b and miR-29c. Collectively, these findings indicate that canine aging is associated with marked changes in plasma EV abundance, morphology, and cargo, indicating that EVs could represent a promising tool for investigating age-related disorders in dogs.

Challenges in estimating wolf population size using spatial count models and camera trap data - M.V. Boiani; P. Dupont; R. Bischof; O. Friard; F. Bisi; G. Bombieri; S. Calderola; S. Carolfi; C. Chioso; U. Fattori; P. Ferrari; S. Filacorda; et al. (Biological Conservation, 2026)

Correction: Training European Health Care Providers in Adolescent and Young Adult (AYA) Oncology: The Joint Action Networks of Expertise (JANE) on AYA with Cancer Perspective - Virginia Livellara; Marina N. Rosanu; Daniel Stark; Annalisa Trama; Salvatore Provenzano; Chiara Prampolini; Paolo G. Casali; Gianluca Vago; Manolis Saloustros; Ian Murphy; Josef H. Vormoor; Katie Rizvi; et al. (Journal of Cancer Education, 2026)

Training European Health Care Providers in Adolescent and Young Adult (AYA) Oncology: The Joint Action Networks of Expertise (JANE) on AYA with Cancer Perspective - Virginia Livellara; Marina N. Rosanu; Daniel Stark; Annalisa Trama; Salvatore Provenzano; Chiara Prampolini; Paolo G. Casali; Gianluca Vago; Emmanouil Saloustros; Ian Murphy; Josef H. Vormoor; Katie Rizvi; et al. (Journal of Cancer Education, 2026)

Beyond phosphorus: five years of evidence for nitrate-limited cyanobacterial blooms in a large subtropical river - C. Bueno; N. Muñoz; K. Bombi-Haedo; L. Marín; A. Cabral; G. Ferrari (Hydrobiologia, 2026)

Yield and protein gaps in barley: Quantifying nitrogen and sulfur contributions - Federico M. Gomez; Flavio H. Gutiérrez-Boem; Pablo Prystupa; Jorge L. Mercau; Jose J. Boero; Gustavo Ferraris; Leonor G. Abeledo (European Journal of Agronomy, 2026)

Multidisciplinary monitoring of mud volcanoes: a new perspective on fluids and seismicity link from the Salse di Nirano (Italy) - E. Ferrari; A. L. Rizzo; G. Capelli Ghioldi; A. Sciarra; G. Tamburello; F. Viveiros; S. Lovati; M. Massa (Natural Hazards, 2026)
Understanding the relationship between fluids and seismicity is crucial for improving seismic hazard assessment, as fluid migration can play a significant role in earthquake triggering. Here, we present the results from an innovative real-time multiparametric monitoring implemented at the so-called ‘Salse di Nirano’ or mud volcano field (Northern Apennines, Italy), a region of medium to high seismic hazard. The objective is to investigate how geofluid dynamics relate to local seismicity. Two bubbling mud pools were selected for continuous monitoring of mud level, temperature, and electrical conductivity. Additionally, a CO 2 flux station was installed on the field’s edge, where elevated gas emissions are observed. Complementary meteorological and seismic stations track atmospheric conditions and seismic activity. Notably, anomalous shifts in mud pool electrical conductivity and soil CO 2 flux were recorded in temporal correlation with two distinct seismic swarms in 2024, highlighting the potential of fluid-geochemistry monitoring as a tool for tracking subsurface processes linked to seismic unrest.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Development of biochar-immobilized Bacillus subtilis BEIB-18 for hexavalent chromium (Cr(VI)) bioremediation in aqueous medium - V. A. Schommer; M. T. Nazari; A. P. Vanin; D. D. C. Krein; N. Melo; L. F. dos Santos; G. L. Dotto; V. Ferrari; L. M. Colla; A. Dettmer; J. S. Piccin (International Journal of Environmental Science and Technology, 2026)

Measurement of the 244Cm neutron capture cross section at the n_TOF facility at CERN - V. Alcayne; A. Kimura; E. Mendoza; D. Cano-Ott; O. Aberle; F. Álvarez-Velarde; S. Amaducci; J. Andrzejewski; L. Audouin; V. Babiano-Suarez; M. Bacak; M. Barbagallo; et al. (Annals of Nuclear Energy, 2026)

Assessment of wildfire-induced hydrological changes in the south andes mountains of chile - G. Alejandra Stehr; V. Nicole Vyhmeister; C. Efraín Duarte; Francisco Nájera-De Ferrari; Vicente Saenger; Felipe Aburto; Rafael Rubilar; Carolina Merino-Guzmán; B. Francisco Matus (Journal of Hydrology, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Sustainable digitalisation - a system thinking approach for determining costs and benefits in the agri-sector - K. Soma; G. Brunori; C. Giagnocavo; F. Meulman; M. Ryan; R.M. Heredia Hortigüela; C. Iliopoulos; M. Paulus; A. Ferrari; E. Kilis; S. Grando; V. Bellon-Maurel; et al. (Agricultural Systems, 2026)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Fibroblast Activation Protein (FAP) as a possible therapeutic target in selected canine malignant tumours - S. Dell'Aere; D. Stefanello; E. Gariboldi; A. Ubiali; R. Ferrari; L. Auletta; M. Bocci; A. Galbiati; S. Cazzamalli; E. Gilardoni; V. Balbi; G. Bianchi; et al. (Journal of Comparative Pathology, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Short-term personal exposure to multiple air pollutants affects nasal microbiota in school-age children - L. Boniardi; G. Solazzo; C. Favero; L. Campo; L. Ferrari; S. Fustinoni (Science of The Total Environment, 2025)

Starch-based hydrogels produced by high-pressure processing (HPP): The effect of high pressure on volume changes - K. Koshenaj; S. Carpentieri; G. Ferrari (Innovative Food Science & Emerging Technologies, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Enhancing wheat yield potential through the QTL QFFE.perg-5A and QFEm.perg-3A associated to spike fruiting efficiency: Insights from plot-level analysis - Nicole Pretini; Leonardo S. Vanzetti; Ignacio I. Terrile; Paula Silva; Giuliana Ferrari; Fernanda G. González (Field Crops Research, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The use of fishery and aquaculture by-products with Nannochloropsis sp. allows total dietary replacement of wild-caught fishmeal, fish oil and soy protein in European sea bass juveniles - A. Marchi; E. Benini; F. Dondi; M.G. Ferrari; D. Scicchitano; G. Palladino; M. Candela; R. Cerri; A. Di Biase; A.J. Vizcaíno; F.J. Alarcón-López; F.G. Acién; et al. (Aquaculture, 2024)

Using stable isotopes to inform water resource management in forested and agricultural ecosystems - Francesca Scandellari; Taha Attou; Adrià Barbeta; Fabian Bernhard; Concetta D’Amato; Katya Dimitrova-Petrova; Amanda Donaldson; Oludare Durodola; Stefano Ferraris; Marius G. Floriancic; Gabriela Fontenla-Razzetto; Malkin Gerchow; et al. (Journal of Environmental Management, 2024)

Enteric associated T-cell lymphoma in a mule - Giovanna G. de Souza; Zara A. Lacerda; Fernanda B.C. de Moura; Isabeli J. Contel; Shéron L. de Oliveira; Lorena C. Ferrari; Emanuel V.P. Apolonio; Juliana de M. Alonso; Ana Liz G. Alves; Noeme S. Rocha (Journal of Equine Veterinary Science, 2024)

Performance of spray nozzles and droplet size on glufosinate deposition and weed biological efficacy - Evandro P. Prado; Júlio C. Guerreiro; Pedro J. Ferreira-Filho; Vagner do Nascimento; Samuel Ferrari; Fernando S. Galindo; Marina Funichello; Carlos G. Raetano; Paulo H. Pagliari; Rodolfo G. Chechetto; Arthur D. Rodrigues Neto (Crop Protection, 2024)

Effect of high-voltage electrical discharge (HVED) at high frequency on vacuum freeze-drying time and physicochemical properties of blueberries - R. Díaz-Álvarez; S. Carpentieri; G. Ferrari; G. Pataro; L. Segura-Ponce (Journal of Food Engineering, 2024)

A Global Systematic Literature Review of Ecosystem Services in Reef Environments - Vinicius J. Giglio; Anaide W. Aued; Cesar A. M. M. Cordeiro; Linda Eggertsen; Débora S. Ferrari; Leandra R. Gonçalves; Natalia Hanazaki; Osmar J. Luiz; André L. Luza; Thiago C. Mendes; Hudson T. Pinheiro; Bárbara Segal; et al. (Environmental Management, 2024)

Evaluation of tire tread particle toxicity to fish using rainbow trout cell lines - W. Dudefoi; B.J.D. Ferrari; F. Breider; T. Masset; G. Leger; E. Vermeirssen; A.J. Bergmann; K. Schirmer (Science of The Total Environment, 2024)

Combination of pH-shifting, ultrasound, and heat treatments to enhance solubility and emulsifying stability of rice protein isolate - Daniela E. Igartúa; M. Celeste Dichano; Sofia B. Ferrari; Gonzalo G. Palazolo; Dario M. Cabezas (Food Chemistry, 2024)

Droplet size and hydraulic spray nozzles in peanut plant spray deposition - Gabriela G. P. Buosi; Arthur D. R. Neto; Paulo R. M. Lopes; Samuel Ferrari; Júlio C. Guerreiro; Pedro J. F. Filho; Ronaldo C. Lima; Vagner Nascimento; Marina Funichello; Carlos G. Raetano; Evandro P. Prado (Journal of Plant Diseases and Protection, 2024)

Effect of an organic acid blend in Nile tilapia growth performance, immunity, gut microbiota, and resistance to challenge against francisellosis - Vanessa Gomes da Silva; Leonardo Mantovani Favero; Raffaella Menegheti Mainardi; Natália Amoroso Ferrari; Roberta Torres Chideroli; Giovana Wingeter Di Santis; Felipe Pinheiro de Souza; Arthur Roberto da Costa; Daniela Dib Gonçalves; Waldo G. Nuez-Ortin; Maria Mercè Isern-Subich; Admilton Gonçalves de Oliveira-Junior; et al. (Research in Veterinary Science, 2023)

Survivin immunohistochemical expression in canine perivascular wall tumours: preliminary assessment - F. Godizzi; F. Armando; A. Cappelleri; P. Boracchi; D. Stefanello; R. Ferrari; L.E. Chiti; A. Corradi; G. Avallone; C. Pigoli; P. Roccabianca (Journal of Comparative Pathology, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Textile microfibers in wild Antarctic whelk Neobuccinum eatoni (Smith, 1875) from Terra Nova Bay (Ross Sea, Antarctica) - E. Bergami; E. Ferrari; M.G.J. Löder; G. Birarda; C. Laforsch; L. Vaccari; I. Corsi (Environmental Research, 2023)

Long-term use of pharmacological treatment in Alzheimer’s disease: a retrospective cohort study in real-world clinical practice - G Lombardi; N Lombardi; A Bettiol; G Crescioli; C Ferrari; G Lucidi; C Polito; V Berti; V Bessi; S Bagnoli; B Nacmias; A Vannacci; et al. (European Journal of Clinical Pharmacology, 2022)

Extinct groundwater discharge locality in the Eldorado Valley; eastern Mojave Desert, Nevada, USA - Douglas B. Sims; Amanda C. Hudson; John E. Keller; Paul McBurnett; David Ferrari; Giavanna M. Fernandez; Juan Garcia-Hernandez; Bailey D. Kesl; Flavio W. Rodriguez; Sean G. Torres (Journal of Sedimentary Environments, 2022)

Peripheral neuropathies during the COVID-19 pandemic: is there a relation? - Milena Trentinaglia; Giuseppe Lippi; Gian Luca Salvagno; Marianna G. Rispoli; Maria Vittoria De Angelis; Francesca Castellani; Daniela Alberti; Giorgia T. Maniscalco; Francesca Rossi; Mara Turri; Patrizia Rossi; Elisabetta Del Zotto; et al. (Immunologic Research, 2022)

Effects of application rate on spray deposition, stink bug control, and yield in soybean crops - José L. C. Santos-Júnior; Carlos G. Raetano; Fernando K. de Carvalho; Pedro J. Ferreira-Filho; Júlio C. Guerreiro; Samuel Ferrari; Vagner Nascimento; Rafael S. Tomaz; Agatha S. Argioli; Evandro P. Prado (Phytoparasitica, 2022)

Protective effect of methyl gallate on murine antigen-induced arthritis by inhibiting inflammatory process and bone erosion - Luana Barbosa Correa; Tatiana Almeida Pádua; Paulo Vinicius Gil Alabarse; Elvira Maria Saraiva; Esdras Barbosa Garcia; Fabio Coelho Amendoeira; Fausto Klabund Ferraris; Sandra Yasuyo Fukada; Elaine Cruz Rosas; Maria G. Henriques (Inflammopharmacology, 2022)

Sensitivity Analysis of Single Beat Left Ventricular Elastance Estimation by Chen Method - A. Di Molfetta; G. Ferrari; V. Cusimano; G. Di Ruzza; P. Mollo; D. Boncompagni; M. Cesario; C. Volponi; M. Massetti; M. Menichelli (Cardiovascular Engineering and Technology, 2022)

New Horizons on Non-invasive Brain Stimulation of the Social and Affective Cerebellum - Z. Cattaneo; C. Ferrari; A. Ciricugno; E. Heleven; D. J. L. G. Schutter; M. Manto; F. Van Overwalle (The Cerebellum, 2021)

Antarctic desert soil bacteria exhibit high novel natural product potential, evaluated through long‐read genome sequencing and comparative genomics - Nicole Benaud; Richard J. Edwards; Timothy G. Amos; Paul M. D'Agostino; Carolina Gutiérrez‐Chávez; Kate Montgomery; Iskra Nicetic; Belinda C. Ferrari (Environmental Microbiology, 2021)
Summary Actinobacteria and Proteobacteria are important producers of bioactive natural products (NP), and these phyla dominate in the arid soils of Antarctica, where metabolic adaptations influence survival under harsh conditions. Biosynthetic gene clusters (BGCs) which encode NPs, are typically long and repetitious high G + C regions difficult to sequence with short‐read technologies. We sequenced 17 Antarctic soil bacteria from multi‐genome libraries, employing the long‐read PacBio platform, to optimize capture of BGCs and to facilitate a comprehensive analysis of their NP capacity. We report 13 complete bacterial genomes of high quality and contiguity, representing 10 different cold‐adapted genera including novel species. Antarctic BGCs exhibited low similarity to known compound BGCs (av. 31%), with an abundance of terpene, non‐ribosomal peptide and polyketide‐encoding clusters. Comparative genome analysis was used to map BGC variation between closely related strains from geographically distant environments. Results showed the greatest biosynthetic differences to be in a psychrotolerant Streptomyces strain, as well as a rare Actinobacteria genus, Kribbella , while two other Streptomyces spp. were surprisingly similar to known genomes. Streptomyces and Kribbella BGCs were predicted to encode antitumour, antifungal, antibacterial and biosurfactant‐like compounds, and the synthesis of NPs with antibacterial, antifungal and surfactant properties was confirmed through bioactivity assays.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Seismological analyses of the seismic microzonation of 138 municipalities damaged by the 2016–2017 seismic sequence in Central Italy - E. Priolo; F. Pacor; D. Spallarossa; G. Milana; G. Laurenzano; M. A. Romano; C. Felicetta; S. Hailemikael; F. Cara; G. Di Giulio; G. Ferretti; C. Barnaba; et al. (Bulletin of Earthquake Engineering, 2020)
This paper describes the seismological analyses performed within the framework of the seismic microzonation study for the reconstruction of 138 municipalities damaged by the 2016–2017 sequence in Central Italy. Many waveforms were recorded over approximately 15 years at approximately 180 instrumented sites equipped with permanent or temporary stations in an area that includes all the damaged localities. Site response was assessed using earthquake and noise recordings at the selected stations through different parameters, such as spectral amplification curves, fundamental resonance frequencies, site-specific response spectra, and average amplification factors. The present study was a collaboration of many different institutions under the coordination of the Italian Center for Seismic Microzonation and its applications . The results were homogenized and gathered into site-specific forms, which represent the main deliverable for the benefit of Italian Civil Protection. It is remarkable that the bulk of this study was performed in a very short period (approximately 2 months) to provide quantitative information for detailed microzonation and future reconstruction of the damaged municipalities.

Type three secretion system in Salmonella Typhimurium: the key to infection - Anamaria M. P. dos Santos; Rafaela G. Ferrari; Carlos A. Conte-Junior (Genes & Genomics, 2020)

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Stereotactic radiation therapy in oligometastatic colorectal cancer: outcome of 102 patients and 150 lesions - V. Dell’Acqua; A. Surgo; F. Kraja; J. Kobiela; Maria Alessia Zerella; P. Spychalski; S. Gandini; C. M. Francia; D. Ciardo; C. Fodor; A. M. Ferrari; G. Piperno; et al. (Clinical & Experimental Metastasis, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Virulence Factors in Salmonella Typhimurium: The Sagacity of a Bacterium - Anamaria M. P. dos Santos; Rafaela G. Ferrari; Carlos A. Conte-Junior (Current Microbiology, 2019)

Marine infrastructure supports abundant, diverse fish assemblages at the expense of beta diversity - A. G. Porter; R. L. Ferrari; B. P. Kelaher; S. D. A. Smith; R. A. Coleman; M. Byrne; W. Figueira (Marine Biology, 2018)

Environmental control of malting barley response to nitrogen in the Pampas, Argentina - P. Prystupa; G. Ferraris; L. Ventimiglia; T. Loewy; L. Couretot; R. Bergh; F. Gómez; F. H. Gutierrez Boem (International Journal of Plant Production, 2018)

Diversity in a pea (Pisum sativum) world collection for key agronomic traits in a rain-fed environment of Southern Europe - P. Annicchiarico; M. Romani; G. Cabassi; B. Ferrari (Euphytica, 2017)

Cadmium effects on some energy metabolism variables in Cnesterodon decemmaculatus adults - Federico G. Baudou; Natalia A. Ossana; Patricia M. Castañé; Martina M. Mastrángelo; Lucrecia Ferrari (Ecotoxicology, 2017)

Prenylated flavonoids and total extracts from Morus nigra L. root bark inhibit in vitro growth of plant pathogenic fungi - G. Simonetti; E. Brasili; F. D. D′Auria; S. Corpolongo; F. Ferrari; G. Pasqua; A. Valletta (Plant Biosystems, 2017)

Perovskite-type titanate zirconate as photocatalyst for textile wastewater treatment - A. M. Ferrari-Lima; A. C. Ueda; E. A. Bergamo; R. G. Marques; E. A. V. Ferri; C. S. Pinto; C. A. A. Pereira; P. H. Yassue-Cordeiro; R. P. Souza (Environmental Science and Pollution Research, 2017)

Impairment of mitochondria dynamics by human A53T α-synuclein and rescue by NAP (davunetide) in a cell model for Parkinson’s disease - T. Q. Melo; K. C. van Zomeren; M. F. R. Ferrari; H. W. G. M. Boddeke; J. C. V. M. Copray (Experimental Brain Research, 2017)

Polymorphisms of dopamine receptor genes and risk of visual hallucinations in Parkinson’s patients - M Ferrari; C Comi; F Marino; L Magistrelli; F De Marchi; R Cantello; G Riboldazzi; G Bono; M Cosentino (European Journal of Clinical Pharmacology, 2016)

”LOVE TO HATE” pesticides: felicity or curse for the soil microbial community? An FP7 IAPP Marie Curie project aiming to establish tools for the assessment of the mechanisms controlling the interactions of pesticides with soil microorganisms - D. G. Karpouzas; G. Tsiamis; M. Trevisan; F. Ferrari; C. Malandain; O. Sibourg; F. Martin-Laurent (Environmental Science and Pollution Research, 2016)

Clinical, hematological, biochemical, and ultrasonographic aspects of Platynosomum sp. (Trematoda: Dicrocoeliidae) infection of captive Callithrix penicillata - Mariana Portugal Mattioli; Juliana dos Santos Batista; Marlon Ferrari; Giane Regina Paludo; Cecília Azevedo Dias; Estevam G. L. Hoppe; Gino Chaves da Rocha; Rafael Veríssimo Monteiro (Primates, 2016)

Biology of the electric eel, Electrophorus electricus, Linnaeus, 1766 (Gymnotiformes: Gymnotidae) on the floodplain of the Curiaú River, eastern Amazonia - Raimundo Nonato G. Mendes-Junior; Júlio César Sá-Oliveira; Stephen F. Ferrari (Reviews in Fish Biology and Fisheries, 2016)

Individual vs. social learning of predator information in fish: does group size affect learning efficacy? - Anthony G. E. Mathiron; Adam L. Crane; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2015)

A unifying gravity framework for dispersal - Eelke Jongejans; Olav Skarpaas; Matthew J. Ferrari; Eric S. Long; Joseph T. Dauer; Carrie M. Schwarz; Emily S. J. Rauschert; Randa Jabbour; David A. Mortensen; Scott A. Isard; David A. Lieb; Zeynep Sezen; et al. (Theoretical Ecology, 2015)

Interactive effects of ocean acidification and rising sea temperatures alter predation rate and predator selectivity in reef fish communities - Maud. C. O. Ferrari; Philip L. Munday; Jodie L. Rummer; Mark I. McCormick; Katherine Corkill; Sue‐Ann Watson; Bridie J. M. Allan; Mark G. Meekan; Douglas P. Chivers (Global Change Biology, 2015)
Ocean warming and acidification are serious threats to marine life. While each stressor alone has been studied in detail, their combined effects on the outcome of ecological interactions are poorly understood. We measured predation rates and predator selectivity of two closely related species of damselfish exposed to a predatory dottyback. We found temperature and CO 2 interacted synergistically on overall predation rate, but antagonistically on predator selectivity. Notably, elevated CO 2 or temperature alone reversed predator selectivity, but the interaction between the two stressors cancelled selectivity. Routine metabolic rates of the two prey showed strong species differences in tolerance to CO 2 and not temperature, but these differences did not correlate with recorded mortality. This highlights the difficulty of linking species‐level physiological tolerance to resulting ecological outcomes. This study is the first to document both synergistic and antagonistic effects of elevated CO 2 and temperature on a crucial ecological process like predator–prey dynamics.

Toxicity and persistence of three pyrethroids for the control of cereal bugs on common wheat - Marco G. Pansa; Massimo Blandino; Barbara L. Ingegno; Ester Ferrari; Amedeo Reyneri; Luciana Tavella (Journal of Pest Science, 2015)

Combination of Pretreatment with White Rot Fungi and Modification of Primary and Secondary Cell Walls Improves Saccharification - Charis Cook; Fedra Francocci; Felice Cervone; Daniela Bellincampi; Paul G Bolwell; Simone Ferrari; Alessandra Devoto (BioEnergy Research, 2015)

Seismicity of Northwestern Italy during the last 30 years - D. Scafidi; S. Barani; R. De Ferrari; G. Ferretti; M. Pasta; M. Pavan; D. Spallarossa; C. Turino (Journal of Seismology, 2015)

The ruthenium nitric oxide donor, [Ru(HEDTA)NO], inhibits acute nociception in mice by modulating oxidative stress, cytokine production and activating the cGMP/PKG/ATP-sensitive potassium channel signaling pathway - Larissa Staurengo-Ferrari; Sandra S. Mizokami; Victor Fattori; Jean J. Silva; Patrícia G. Zanichelli; Sandra R. Georgetti; Marcela M. Baracat; Luiz G. da França; Wander R. Pavanelli; Rubia Casagrande; Waldiceu A. Verri (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Latitudinal pattern in plant composition along the Peruvian and Chilean fog oases - R. Manrique; C. Ricotta; C. Ferrari; G. Pezzi (Plant Biosystems, 2014)

Biodegradation of ballast tank coating investigated by impedance spectroscopy and microscopy - A. Heyer; F. D’Souza; X. Zhang; G. Ferrari; J. M. C. Mol; J. H. W. de Wit (Biodegradation, 2014)

Impaired learning of predators and lower prey survival under elevated CO 2 : a consequence of neurotransmitter interference - Douglas P. Chivers; Mark I. McCormick; Göran E. Nilsson; Philip L. Munday; Sue‐Ann Watson; Mark G. Meekan; Matthew D. Mitchell; Katherine C. Corkill; Maud C. O. Ferrari (Global Change Biology, 2014)
Ocean acidification is one of the most pressing environmental concerns of our time, and not surprisingly, we have seen a recent explosion of research into the physiological impacts and ecological consequences of changes in ocean chemistry. We are gaining considerable insights from this work, but further advances require greater integration across disciplines. Here, we showed that projected near‐future CO 2 levels impaired the ability of damselfish to learn the identity of predators. These effects stem from impaired neurotransmitter function; impaired learning under elevated CO 2 was reversed when fish were treated with gabazine, an antagonist of the GABA ‐A receptor – a major inhibitory neurotransmitter receptor in the brain of vertebrates. The effects of CO 2 on learning and the link to neurotransmitter interference were manifested as major differences in survival for fish released into the wild. Lower survival under elevated CO 2 , as a result of impaired learning, could have a major influence on population recruitment.

Chemical composition and antifungal activity of Hypericum perforatum subsp. angustifolium roots from wild plants and plants grown under controlled conditions - N. Tocci; G. Simonetti; F. D. D'Auria; S. Panella; A. T. Palamara; F. Ferrari; G. Pasqua (Plant Biosystems, 2013)

Gait analysis in children with cerebral palsy via inertial and magnetic sensors - Josien C. van den Noort; Alberto Ferrari; Andrea G. Cutti; Jules G. Becher; Jaap Harlaar (Medical & Biological Engineering & Computing, 2013)

Retention of acquired predator recognition among shy versus bold juvenile rainbow trout - G. E. Brown; M. C. O. Ferrari; P. H. Malka; L. Fregeau; L. Kayello; D. P. Chivers (Behavioral Ecology and Sociobiology, 2013)

Fruits of Mimosa foliolosa (Fabales: Fabaceae) as Sleeping Shelter for Megachile (Pseudocentron) botucatuna (Hymenoptera: Megachilidae) - G W Fernandes; R R Ferrari (Neotropical Entomology, 2012)

Do fathead minnows, Pimephales promelas Rafinesque, alter their club cell investment in responses to variable risk of infection from Saprolegnia ? - R J Pollock; M S Pollock; M C O Ferrari; S G W Kaminskyj; D P Chivers (Journal of Fish Diseases, 2012)
Fish in the Superorder Ostariophysi possess large epidermal club cells that release chemical cues warning nearby conspecifics of danger. Despite the long‐held assumption that such club cells evolved under the selective force of predation, recent studies demonstrated that predation has no effect on club cell investment. Rather, club cells have an immune function and cell production may be stimulated by skin‐penetrating pathogens and parasites. The current work investigates whether fathead minnows, Pimephales promelas , alter their club cell characteristics based on variation in infection risk. In a 2 × 3 design, we exposed minnows to infective cysts of two oomycete species ( Saprolegnia ferax and S. parasitica ) at three different concentrations (2, 20 or 200 cysts L −1 ). Club cell characteristics (number and size) were quantified 12 days after exposure. Saprolegnia parasitica is thought to be more pathogenic than S. ferax , hence we predicted greater club cell investment and a larger turnover rate of cells by minnows exposed to S. parasitica than S. ferax. We also predicted that minnows exposed to higher numbers of cysts should invest more in club cells and have a higher turnover rate of cells. We found no difference in club cell density or size between fish exposed to the two Saprolegnia species; however, fish exposed to high concentrations of pathogens had smaller club cells than those exposed to low concentrations, indicating a higher rate of turnover of cells in the epidermis.

Intrageneric variation in antipredator responses of coral reef fishes affected by ocean acidification: implications for climate change projections on marine communities - MAUD C. O. FERRARI; DANIELLE L. DIXSON; PHILIP L. MUNDAY; MARK I. McCORMICK; MARK G. MEEKAN; ANDREW SIH; DOUGLAS P. CHIVERS (Global Change Biology, 2011)
Our planet is experiencing an increase in the concentration of atmospheric carbon dioxide (CO 2 ) unprecedented in the past 800 000 years. About 30% of excess atmospheric CO 2 is absorbed by the oceans, thus increasing the concentration of carbonic acid and reducing the ocean's pH. Species able to survive the physiological stress imposed by ocean acidification may still suffer strong indirect negative consequences. Comparing the tolerance of different species to dissolved CO 2 is a necessary first step towards predicting the ecological impacts of rising CO 2 levels on marine communities. While it is intuitive that not all aquatic species will be affected the same way by CO 2 , one could predict that closely related species, sharing similar life histories and ecology, may show similar tolerance levels to CO 2 . Our ability to create functional groups of species according to their CO 2 tolerance may be crucial in our ability to predict community change in the future. Here, we tested the effects of CO 2 exposure on the antipredator responses of four damselfish species ( Pomacentrus chrysurus, Pomacentrus moluccensis, Pomacentrus amboinensis and Pomacentrus nagasakiensis ). Although being sympatric and sharing the same ecology and life history, the four congeneric species showed striking and unexpected variation in CO 2 tolerance, with CO 2 ‐induced loss of response to predation risk ranging from 30% to 95%. Using P. chrysurus as a model species, we further tested if these behavioural differences translated into differential ability to survive predators under natural conditions. Our results indicate that P. chrysurus larvae raised under CO 2 levels predicted by 2070 and 2100 showed decreased antipredator responses to risk, leading to a five‐ to sevenfold increase in predation‐related mortality in the first few hours of settlement. Examining ocean acidification, along with other environmental variables, will be a critical step in further evaluating ecological responses to predicted climatic change.

Use of a comprehensive numerical model to improve biventricular pacemaker temporization in patients affected by heart failure undergoing to CRT-D therapy - A. Di Molfetta; L. Santini; G. B. Forleo; M. Cesario; C. Tota; M. Sgueglia; D. Sergi; G. Ferrari; F. Romeo (Medical & Biological Engineering & Computing, 2010)

Relationship between body fat and body condition score and their effects on estrous cycles of the Standardbred maiden mare - I. Vecchi; A. Sabbioni; E. Bigliardi; G. Morini; L. Ferrari; F. Di Ciommo; P. Superchi; E. Parmigiani (Veterinary Research Communications, 2010)

Chronic variable stress impairs energy metabolism in prefrontal cortex and hippocampus of rats: prevention by chronic antioxidant treatment - Bárbara Tagliari; Cristie G. Noschang; Andréia G. K. Ferreira; Otávio A. Ferrari; Luciane R. Feksa; Clovis M. D. Wannmacher; Carla Dalmaz; Angela T. S. Wyse (Metabolic Brain Disease, 2010)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

Monitoring and assessing old‐growth forest stands by plot sampling - P. Corona; C. Blasi; G. Chirici; L. Facioni; L. Fattorini; B. Ferrari (Plant Biosystems, 2010)

Chitosan enhances xanthone production in Hypericum perforatum subsp. angustifolium cell cultures - N. Tocci; F. Ferrari; A.R. Santamaria; A. Valletta; I. Rovardi; G. Pasqua (Natural Product Research, 2010)

Detection of porcine circovirus type 2 (PCV2) from wild boars in central Italy - S. Petrini; S. Barocci; S. Gavaudan; R. Villa; S. Briscolini; M. Sabbatini; C. Mattozzi; F. Barchiesi; S. Salamida; M. Ferrari; M. Paniccià; G. Pezzotti (European Journal of Wildlife Research, 2009)

Dexmedetomidine chemical restraint of two raptor species undergoing inhalation anaesthesia - B. Santangelo; D. Ferrari; I. Di Martino; A. Belli; C. Cordella; A. Ricco; S. Troisi; G. Vesce (Veterinary Research Communications, 2009)

Social context, competitive interactions and the dynamic nature of antipredator responses of juvenile rainbow trout Oncorhynchus mykiss - G. E. Brown; M. C. Harvey; A. O. H. C. Leduc; M. C. O. Ferrari; D. P. Chivers (Journal of Fish Biology, 2009)
The effects of food ration and social context, as well as possible interactions, on the antipredator behaviour of juvenile rainbow trout Onchorhynchus mykiss were investigated in a pair of laboratory studies. In experiment 1, pairs of dominant and subordinate O. mykiss were exposed to conspecific alarm cues when maintained under high or low food rations. Under high food rations, dominant individuals responded to predation risk, whereas subordinates used the opportunity to feed. Under low food ration, however, the opposite pattern was observed, where subordinates responded to predation cues and dominants did not. Experiment 2 consisted of performing the same experiment, however separating the dominant and subordinate O. mykiss 3 h before testing. When tested separately, dominant and subordinate individuals did not differ in their responses to alarm cues, regardless of food ration. These results demonstrate that there is a complex interaction between current energy status and social context on decision making by prey animals.

An alternative method to isoenzyme profile for cell line identification and interspecies cross-contaminations: cytochrome b PCR-RLFP analysis - Claretta G Losi; Stefania Ferrari; Enrico Sossi; Riccardo Villa; Maura Ferrari (In Vitro Cellular & Developmental Biology - Animal, 2008)

A comparison of the humoral and cell-mediated response of pigs experimentally infected with either influenza or PRRS viruses - M. Ferrari; P. Candotti; G. Lombardi; M. Amadori; S. Dotti; S. Guana; S. Petrini (Veterinary Research Communications, 2008)

Productive and metabolic consequences induced by the retained placenta in dairy cows - E. Trevisi; A. R. Ferrari; G. Bertoni (Veterinary Research Communications, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Adult Stem Cells: Perspectives for Therapeutic Applications - M. Ferrari; A. Corradi; M. Lazzaretti; M. De’Cillà; C. G. Losi; R. Villa; A. Lanfranchi (Veterinary Research Communications, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Preservation methods of Tolypothrix tenuis for use as a cyanobacterial fertilizer - Patricia G. Silva; Susana G. Ferrari; Humberto J. Silva (Journal of Applied Phycology, 2007)

Imported malaria at Italy’s National Institute for Infectious Diseases Lazzaro Spallanzani, 1984–2003 - F. Spinazzola; E. Nicastri; C. Vlassi; P. Ghirga; M. Marco; S. Pittalis; M. G. Paglia; C. Ferrari; P. Narciso (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Nodulation and growth of black locust (Robinia pseudoacacia) on a desurfaced soil inoculated with a local Rhizobium isolate - Alejandro E. Ferrari; Luis G. Wall (Biology and Fertility of Soils, 2007)

Relationship of alcohol intake and sex steroid concentrations in blood in pre- and post-menopausal women: the European Prospective Investigation into Cancer and Nutrition - S. Rinaldi; P. H. M. Peeters; I. D. Bezemer; L. Dossus; C. Biessy; C. Sacerdote; F. Berrino; S. Panico; D. Palli; R. Tumino; K. T. Khaw; S. Bingham; et al. (Cancer Causes & Control, 2006)

An Immunoenzyme Linked Assay (ELISA) for the Detection of Antibodies to Truncated Glycoprotein D (tgD) of Bovine Herpesvirus-1 - S. Petrini; M. Ferrari; S. Vincenzetti; A. Vita; A. Amici; G. Ramadori (Veterinary Research Communications, 2006)

Volcanic Tremor at Mt. Etna, Italy, Preceding and Accompanying the Eruption of July – August, 2001 - S. Falsaperla; S. Alparone; S. D'Amico; G. Di Grazia; F. Ferrari; H. Langer; T. Sgroi; S. Spampinato (Pure and Applied Geophysics, 2005)

Volcanic Tremor at Mt. Etna, Italy, Preceding and Accompanying the Eruption of July – August, 2001 - S. Falsaperla; S. Alparone; S. D’Amico; G. Grazia; F. Ferrari; H. Langer; T. Sgroi; S. Spampinato (Pure and Applied Geophysics, 2005)

Study on the Virulence, Cell-mediated Immune Response and Histolesivity of Three Field PRRSV Strains with an ORF 5 Genetic Variation - A. Corradi; M. Ferrari; A. M. Cantoni; C. Robotti; L. Alborali; R. Di Lecce; P. Candotti; G. P. Sandri; P. Borghetti (Veterinary Research Communications, 2005)

Vaccination Trials Against Bovine Herpesvirus-1 - G. Castrucci; M. Ferrari; D. Salvatori; S. Sardonini; F. Frigeri; S. Petrini; M. Lo Dico; C. Marchini; A. Rotola; A. Amici; M. Provinciali; A. Tosini; et al. (Veterinary Research Communications, 2005)

X-linked heterochromatin distribution in the holocentric chromosomes of the green apple aphid Aphis pomi - A. Criniti; G. Simonazzi; S. Cassanelli; M. Ferrari; D. Bizzaro; G. C. Manicardi (Genetica, 2005)

Recognition and signalling in the cell wall: The case of endopolygalacturonase, PGIP and oligogalacturonides - B Mattei; R Galletti; C Manfredini; D Pontiggia; G Salvi; S Spadoni; C Caprari; S Ferrari; D Bellincampi; F Cervone; G De Lorenzo (Plant Biosystems, 2005)

Loading of nutrient from a land-based fish farm(Orbetello, Italy) at different times - S. Porrello; M. Lenzi; G. Ferrari; E. Persia; F. Savelli; P Tomassetti (Aquaculture International, 2005)

New Minerals Approved in 2003 and Nomenclature Modifications Approved in 2003 by the Commission on New Minerals and Mineral Names, International Mineralogical Association - E. A. J. Burke; G. Ferraris (Mineralogy and Petrology, 2004)

NEW MINERALS APPROVED IN 2002 NOMENCLATURE MODIFICATIONS APPROVED 1998?2002 BY THE COMMISSION ON NEW MINERALS AND MINERAL NAMES INTERNATIONAL MINERALOGICAL ASSOCIATION - J. D. Grice; G. Ferraris (Mineralogy and Petrology, 2004)

Preliminary Studies on Compatibility between High Yield Levels and the Well-being of Dairy Cows - G. Bertoni; E. Trevisi; A. Ferrari; I. Archetti (Veterinary Research Communications, 2003)

Kristiansenite, a new calcium-scandium-tin sorosilicate from granite pegmatite in Tørdal, Telemark, Norway - G. Raade; G. Ferraris; A. Gula; G. Ivaldi; F. Bernhard (Mineralogy and Petrology, 2002)

Chemical Ecological Characteristics of Herbivory of Siparuna guianensis Seeds by Buffy-Headed Marmosets (Callithrix flaviceps) in the Atlantic Forest of Southeastern Brazil - Naomi K. Simas; Stephen F. Ferrari; Sonia N. Pereira; Gilda G. Leitão (Journal of Chemical Ecology, 2001)

Is a Kit for Identification of Clinical Yeasts Correctly Evaluated When Released onto the Market? - A. M. Tortorano; F. Barchiesi; E. Manso; M. T. Montagna; C. Farina; L. Ferrari; A. Raballo; A. Grancini; G. Lombardi (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Relationship between sediment distribution and Posidonia oceanica seagrass - G. De Falco; S. Ferrari; G. Cancemi; M. Baroli (Geo-Marine Letters, 2000)

Titi monkeys (Callicebus spp., Atelidae: Platyrrhini) in the Brazilian state of Rondônia - Stephen F. Ferrari; Simone Iwanaga; Mariluce R. Messias; Eleildon M. Ramos; Paulo C. S. Ramos; Ernesto H. da Cruz Neto; Paulo E. G. Coutinho (Primates, 2000)

Zoogeography of Chiropotes albinasus (Platyrrhini, Atelidae) in Southwestern Amazonia - Stephen F. Ferrari; Simone Iwanaga; Paulo E. G. Coutinho; Mariluce R. Messias; Ernesto H. Cruz Neto; Eleildon M. Ramos; Paulo C. S. Ramos (International Journal of Primatology, 1999)

Synchrotron powder diffraction study of phengite 3T from the Dora-Maira massif: P - V - T equation of state and petrological consequences - A. Pavese; G. Ferraris; V. Pischedda; M. Mezouar (Physics and Chemistry of Minerals, 1999)

Preface - G. Ferraris; W. Petruk; E. F. Stumpfl (Mineralogy and Petrology, 1999)

Acetylcholinesterase assay may predict cognitive response of Alzheimer patients to eptastigmine treatment - B. P. Imbimbo; M. Nicoli; C. Martini; G. P. Tomelleri; P. Martelli; G. P. Ferrari; G. Gambina (European Journal of Clinical Pharmacology, 1998)

P-V equation of state of portlandite, Ca(OH) 2 , from powder neutron diffraction data - A. Pavese; M. Catti; G. Ferraris; S. Hull (Physics and Chemistry of Minerals, 1997)

Cytogenetic biomonitoring of styrene-exposed plastic boat builders - M. Artuso; G. Angotzi; S. Bonassi; S. Bonatti; M. De Ferrari; D. Gargano; L. Lastrucci; L. Miligi; C. Sbrana; A. Abbondandolo (Archives of Environmental Contamination and Toxicology, 1995)

Isolation and characterization of cytopathic strains of rotavirus from rabbits - G. Castrucci; M. Ferrari; F. Frigeri; V. Cilli; L. Perucca; G. Donelli (Archives of Virology, 1985)

Reactivation in calves ofBovid herpesvirus 2 latent infection - G. Castrucci; M. Ferrari; F. Frigeri; S. Ranucci; V. Cilli; B. Tesei; L. Rampichini (Archives of Virology, 1982)